Impact of Microwave Treatment on Paneer: A Study of Image Analysis and Quality - Sinha, Chitranayak; M, Manjunatha; Minz, PS; John, Hima; Kumari, Khushbu; ., Priyanka (Indian Journal of Dairy Science, 2025)
The image processing technique was employed to analyze microwave-treated paneer samples. These samples were prepared through the standard heat-coagulation process of milk to produce paneer. A microprocessor-controlled semi-automatic pressing technique was utilized for paneer pressing, and its textural parameters were assessed using image-analysis methods. Microwave heating was introduced to extend the shelf-life of the paneer. Subsequently, paneer samples were placed in a 50 mm diameter dish and scanned using a Canon scan Mark II 9000F scanner to analyze colour parameters. The structure visible in the images was evaluated both before and after microwave treatment. It was observed that longer durations of microwave heating affected the browning index, while shorter exposures did not significantly enhance shelf life. The microbial quality shelf-life of microwave-heated paneer samples was extended by up to 15 additional days compared to control samples.